Transformational Leadership and Professional Learning Communities: A Synergistic Approach to Developing Teachers' Pedagogical Competence - Elmiwarti Indriani; Fadly Azhar; Dedi Futra (Papanda Publisher, 2026)
Teacher pedagogical competence remains a critical concern in Indonesia's educational landscape, particularly during the implementation of the Merdeka Curriculum. While transformational leadership and professional learning communities have been identified as influential factors, limited research has examined their combined effects in rural contexts. This study investigated the individual and simultaneous influence of school principals' transformational leadership and Ruang GTK learning community engagement on teachers' pedagogical competence in junior high schools. Employing an explanatory quantitative design, this study utilized census sampling involving all 75 teachers from four junior high schools in Koto Gasib District, Riau Province. Data were collected using validated Likert-scale questionnaires and analyzed through multiple linear regression. Both transformational leadership (β = 0.212, p = 0.002) and learning community engagement (β = 0.489, p = 0.000) significantly influenced pedagogical competence. Simultaneously, these variables explained 61.3% of the variance in pedagogical competence (R² = 0.613, F = 57.146, p = 0.000). A strong correlation between transformational leadership and learning communities (r = 0.763) revealed a synergistic relationship. Learning communities demonstrated stronger direct effects than transformational leadership on pedagogical competence. The synergistic relationship between both factors suggests that integrated interventions targeting leadership development and collaborative learning platforms yield optimal outcomes for enhancing teacher quality during curriculum reform implementation in resource-constrained settings.